Global data management - Baldoni, Roberto (Emerging communication, 2006)
Some researcher has created the vision of the 'data utility' as a key enabler towards ubiquitous and pervasive computing. Decentralization and replication would be the approach to make it resistant against security attacks. This book presents an organic view on the research and technologies, which bring us towards the realization of the vision.